Insights into the current management of dyslipidemia from a clinical pharmacological perspective - Le, Chuyen; Nguyen, Thi Lan Nhi; Nguyen, Le Hong Van; Do, Thi Hong Diep; Dang, Thi Cat Vy (Tạp chí Y Dược Huế, 2023)
The low-density lipoprotein cholesterol (LDL-C) is established as a causative agent of atherosclerotic cardiovascular disease (ASCVD) and lowering plasma LDL-C levels represents the main approach to reduce the risk of cardiovascular events. Statins remain the cornerstone of drug therapy for dyslipidemia. Although moderate- to high- intensity statin therapy has demonstrated consistent benefits for secondary prevention of cardiovascular events, statin monotherapy is insufficient to achieve the guideline-recommended LDL-C levels for high- and very high-risk patients. Some patients cannot tolerate statins, especially when taking long-term high doses. Several non-statin drugs that have a complementary mechanism of action to statins are now available, including ezetimibe, monoclonal antibodies targeted to proprotein convertase subtilisin/ kexin type 9 (PCSK9 mAb), and, more recently, inclisiran, bempedoic acid, and evinacumab. Considering the recommendations from guidelines by domestic and international cardiovascular associations, combining these drugs should be contemplated to attain treatment goals for patients.